ANAYSIS ON GRAMMATICALITY OF STUDENTS’ WRITING ASSIGNMENTS - Kardianto, Arry; Sudarsono, Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to find out the most dominant ungrammatical forms made by the students of Year-10 in SMA Negeri 10 Pontianak in academic year 2016/2017. The researcher applied descriptive research as the method. In order to answer the research problem, the researcher conducted several steps to find out the ungrammatical forms. First, the researcher collected the corpus as the source of the data. After that, the researcher sorted out the data that contain ungrammatical forms and calculated the total of ungrammatical forms. In this research, the ungrammatical, the researcher divided the ungrammatical forms into ungrammatical phrase and ungrammatical clause. Total ungrammatical phrases made by the students are 126 with ungrammatical noun phrase dominated it. The ungrammatical clauses are 233 times made by the students with ungrammatical nonfinite verb as the most dominant ungrammatical form encountered. This research covered the needs both teacher and students what are going to with result and as the reflection for better teaching learning process especially grammar in English. Keywords: Analysis, Grammaticality, Students’ Writing